الاغتراب و مفاهيمه النفسية و الاجتماعية - الصائغ، محمد ذنون زينو Alsayegh, Mohammed Dhanoun Zinou (جامعة الموصل - كلية الآداب, 2013)
Defining the conceptions and terminology is a necessary matter for scientific research, and for researcher, in forming a theme or a problem. He has to define the conceptions he uses. And as far as this definition characterized by accuracy and clarity the more it facilitates the realizations of meanings and thoughts for the specialized readers who pursuit the research, in addition to the unspecialized persons, particularly the hypotheses, theories and the findings which the researcher wants to express without misunderstanding of what he is saying. If a concept definition is a must in the scientific researches, generally, the social research in particular requires, also, to define the scientific concepts that research deals with in addition to its definition and explanation, where as these concepts are regarded as the basic support of the research, which the researcher can through it define and draw a clear image about the subject of the research and its objectives. \ But the Humanitarian sciences, including the social sciences suffers from fusions and vagueness in defining a large umber of terminology. Some of them as an example is the "Alienation" concept, which considered as one of the most controversial concepts and subjects, not only due to the ambiguity of its meaning, but also, due to numerous definitions given to it, its extension, and its usages, in addition to the numerous orientations and the humanitarian sciences which dealt with it by research and analysis: all what can't hide the fact that, that it is not impossible to define this concept, but there is no escape of saying that the process has some sort of difficulty, and it remains a matter of personal point of view. But the theme is waiting for the others to try their solutions toward that. \ Upon that we tried, in this research to define and identify the "Alienation concept" in addition to other concepts linked to this theme such as the social alienation, behavioral alienation, and personality alienation.
Keywords: علم الاجتماع -- الاغتراب النفسي -- العزلة الاجتماعية -- البحوث الاجتماعية